2000
DOI: 10.1046/j.1365-2168.2000.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of arteriovenous fistulas using transposed autologous basilic vein

Abstract: In high-risk patients the autologous transposed brachiobasilic fistula has equivalent patency and lower complication rates than those reported for polytetrafluoroethylene interposition grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
51
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 15 publications
9
51
1
3
Order By: Relevance
“…We could not find this correlation and calculated excellent 1 and 2 year secondary patencies compared with those reported in the literature (47-92 and 41-86%, respectively) [8,9,[12][13][14][15]. This high secondary patency underlines the functionality of the BB-AVF and may be enhanced by access surveillance.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…We could not find this correlation and calculated excellent 1 and 2 year secondary patencies compared with those reported in the literature (47-92 and 41-86%, respectively) [8,9,[12][13][14][15]. This high secondary patency underlines the functionality of the BB-AVF and may be enhanced by access surveillance.…”
Section: Discussioncontrasting
confidence: 43%
“…The longer period needed before the newly created fistula can be cannulated in the case of the two-stage procedure might be a disadvantage. Although 80% of the patients had a previous vascular access, the non-maturation was low (3%) compared with those reported in the literature (15-38%) [8,9]. An explanation could be that in the case of a previous ipsilateral forearm vascular access, the basilic vein diameter has already been increased.…”
Section: Discussionmentioning
confidence: 45%
“…Literatürde SV greft ve BVT ile ikincil AVF oluşturulmasının etkinlik ve açık kalım üzerine karşılaştırılmasını amaçlayan çalışmaya rastlanmamıştır. BVT ile yapılan muhtelif çalışmalarda (13,14,15,16) BVT'nin ikincil AVF oluşturulmasında iyi bir seçenek oluşturduğu vurgulanmıştır. Basilik ven (BV) üst ekstremitedeki derin yerleşimine bağlı olarak iatrojenik hasarlanmalara karşı çoğu kez korunmuş durumdadır.…”
Section: Discussionunclassified
“…Dagher et al (10) reported the first series of BVT in 1976. Since that time, multiple studies have reported a wide range of long-term patency results for BVT (4,6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Gormus et al (25) have shown no significant differences between forearm and upper arm BVT.…”
Section: Discussionmentioning
confidence: 99%